Molecular Characterization of Carbapenem-Resistant Enterobacter cloacae in 11 Chinese Cities - Jin, Chunmei; Zhang, Jiangang; Wang, Qi; Chen, Hongbin; Wang, Xiaojuan; Zhang, Yawei; Wang, Hui (Frontiers in Microbiology, 2018)
Carbapenem-resistant Enterobacteriaceae (CRE) are usually resistant to most of antibiotics. Infections caused by such bacteria have a high mortality and pose a serious threat to clinical management and public health. Enterobacter cloacae ranks third among Enterobacteriaceae that cause nosocomial infections. In this study, the molecular characteristics of carbapenem-resistant E. cloacae in China were investigated. From November 2012 to August 2016, 55 non-repetitive strains of carbapenem-resistant E. cloacae were collected from 12 hospitals in 11 Chinese cities. The bacteria were identified with matrix-assisted laser desorption/ionization time of flight mass spectrometry. Antimicrobial susceptibility tests were determined by agar dilution method. Carbapenemase and other β-lactamase genes were detected with PCR and sequencing. Multilocus sequence typing and plasmid conjugation tests were performed. Among the 55 E. cloacae strains, 50 strains were detected to produce 8 types of carbapenemase including NDM-1, NDM-5, IMP-4, IMP-26, IMP-1, KPC-2, and VIM-1. NDM-1 accounted for 68.0% (34/50) among the carbapenemase-producing E. cloacae. A total of 24 sequence types were identified and ST418 was the most common, accounting for 20% (11/55). For further investigation, a pulsed-field gel electrophoresis (PFGE) assay was conducted to identify the PFGE patterns of the strains. These 23 isolates yielded 13 PFGE patterns, which were designated as type A–M. Eight isolates obtained from Shenzhen had the same PFGE pattern (type A) and the remaining 15 isolates belonged to the other 12 PFGE patterns (type B–M). The observation that 8 of the 15 blaNDM−1-positive E. cloacae isolates obtained from Shenzhen with the same PFGE pattern (type A) suggested a transmission outbreak of a common strain. S1-nuclease PFGE and Southern blotting were also conducted to estimate the size of plasmids harbored by blaNDM−1-positive strains. The results showed that the plasmids harboring the blaNDM−1 gene ranged in size from approximately 52–58 kilobases. Our study indicates that carbapenem-resistant E. cloacae strains that produce NDM carbapenemase have strong resistance. Early detection and monitoring of the prevalence of these strains are urgent.